Faktor-Faktor Yang Mempengaruhi Kinerja Sistem Informasi Akuntansi (Survey pada PD.BPR BKK PURWODADI) - Susanti, Siti; , Dr. Noer Sasongko, S.E., MS.i., Ak (2015)
The competitive ability of a company to do when management is able to make decisions that are based on a quality information. A quality information will be formed from the existence of a systeminformation (SI), which has been well designed. Proper use of information systems and is supported by the ability to operate the personal technique can improvethe performance of the company and the individual concerned. The purpose of this study was to determine the factors that affect system performance information on PD. BPR BKK PURWODADI. This research is quantitative descriptive, the population in this study is the PD. BPR BKK PURWODADI who use accounting information system. The sample in this study were all employees of PD. BPR BKK PURWODADI who use accounting information system. The study involved 46 respondents who exist in PD. BPR BKK PURWODADI. Data obtained through questionnaires directly to the object of research. The sampling technique used in this study is Convinience Sampling. Analysis of the data used in this research is multiple linear regression, t-test, F test, and test the coefficient of determination (R2). Based on the results of multiple linear regression analysis regression equation KSIA = 11.504+ 1.418KP + 0.533KTP + 0.779DTM + 0.895PP + ε. T test results obtained user involvement variable results of 0000, variable personal technical capability of 0001, variable top management support for 0035, the variable training and user education by 0013. means that all variables are statistically significant effect on the performance of the accounting information system. While the F test results obtained from Fhitung (15 612)> Ftabel (2:57), then the model is in conformity with the theorized. As such variable user involvement, personal technical ability, top management support, training and user education together have an influence on the performance of the accounting information system.